ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU R DI PRAKTIK MANDIRI BIDAN ERLIZA KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Sri Bina Hayati; Anna Malia; Sri Raudhati (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction Comprehensive midwifery care is care provided by midwives to clients starting from pregnancy, childbirth, newborns, postpartum and contraception. The maternal mortality rate in Indonesia is still relatively high and a big problem as a developing country. One of the efforts to reduce the mortality rate is to provide antenatal care services for monitoring and detection during pregnancy, maternal care during childbirth, detection of bleeding, infection and hypertension. The purpose of this case study is to be able to provide Comprehensive Midwifery Care to Mrs. R at PMB Erliza. Method The case study method used is an observational case study using qualitative data, which was conducted at PMB Erliza, Peusangan District, Bireuen Regency in February-June 2021. The subject in this case study was mother R aged 35 years G5P2A2 starting from pregnancy, childbirth, baby newborn, puerperium and contraception. Result The comprehensive midwifery care that was carried out on Mrs. R did not find any complications or complications that accompanied Mrs. R during pregnancy, childbirth, postpartum, her baby and the use of contraception. Midwifery care during pregnancy was carried out twice, delivery during the hour, postpartum was carried out 4 visits, newborns 3 visits and the mother chose to use natural contraception with the MAL method so as not to interfere with breast milk production. Conclusion Comprehensive midwifery care for Mrs. R at PMB Erliza has been carried out in accordance with midwifery care standards and no complications or complications were found during pregnancy, childbirth, postpartum, newborn and contraception.